Bioconversion of carbon dioxide in anaerobic digesters for on-site carbon capture and biogas enhancement - A review - Bajón Fernández, Yadira; Soares, Ana; Koch, Konrad; Vale, Peter C. J.; Cartmell, Elise (Taylor & Francis, 2017)
Energy consumption of the water sector presents an increasing energy demand, contrary to GHG mitigation aims. As a result, research aimed at capturing emitted CO2 and at developing treatment technologies with a low energy demand and increased renewable energy production has increased, leading to a surge in implementation of anaerobic digestion (AD). Valorization of the biogenic CO2 emitted with biogas AD (estimated at over 1 MtCO2 per annum for the UK water and organic waste sectors), presents an opportunity to further reduce carbon footprint and support energy supply decarburization. This paper reviews bioconversion of CO2 into CH4 in ADs (without addition of H2) as a means to valorize CO2 emissions. The review has concluded this to be a promising solution to reduce carbon footprint and uplift renewable energy production. However, in order to increase readiness for implementation (1) the mechanisms of CO2 utilization need to be elucidated, including the sources of additional H2 needed, (2) studies need to report more thoroughly the conditions of CO2 injection and (3) trials where ADs are integrated with gas to liquid mass transfer technologies need to be performed.
Keywords: Anaerobic digestion; Bioconversion; Carbon dioxide; greenhouse gas; Valorization